An Impedance-Controlled Knee Orthosis for Assisted Sit-to-Stand - Scheidl, Marc-Anton; Akarsu, İsmail Berkay and Mehrkens, Florian and Czierlinski, Belinda and Castellini, Claudio (Converging Clinical and Engineering Research on Neurorehabilitation V. Proceedings of the 6th International Conference on Neurorehabilitation (ICNR 2024), November 5–8, 2024, La Granja, Spain - Volume 1, 2025)
This work presents a study investigating the use of an impedance-controlled knee orthosis to assist with sit-to-stand transitions by leveraging EMG signals. A modified knee orthosis equipped with an electric actuator and an EMG bracelet enabled EMG-based impedance control. The results show altered velocity peaks with assistive support, indicating less strenuous movement. Further, EMG muscle activity was reduced significantly, suggesting lower physical effort required for the task. These findings demonstrate the potential of smart orthoses to optimize energy efficiency and enhance rehabilitation outcomes by dynamically adjusting joint impedance based on EMG activity.
CRIS-Team Scopus Importer:2025-03-28
Keywords: electromyography; impedance control; Knee orthosis; rehabilitation; Sit-to-stand transitions